European memory clinic clinicians' preferences and needs for communication with patients: Presenter(s): Heleen Hendriksen, Alzheimer Center Amsterdam, Amsterdam Neuroscience, Vrije Universiteit Amsterdam, Amsterdam UMC, Amsterdam, Netherlands. (April 2023) - van Gils, Aniek; Kivipelto, Miia; Mangialasche, Francesca; Rhodius-Meester, Hanneke; Smets, Ellen; van der Flier, Wiesje; Visser, Leonie
Abstract : Background: Increased attention to pre-dementia stages of Alzheimer's disease (AD) creates new challenges for clinician-patient communication. To assist clinicians, we aimed to: 1) identify their perspectives on communicating about AD-biomarker results, dementia risk, and prevention, and 2) inventory their need for communication support. Methods: Between June and November 2021, 160 memory clinic clinicians from 21 European countries (56% 31-50 yrs; 59% female, 14±10 yrs of experience) completed a survey in which they provided their opinions based on five hypothetical patient cases in different stages of AD, i.e., subjective cognitive decline (SCD) and mild cognitive impairment (MCI) with/without presence of AD-biomarkers, and AD dementia. Additionally, we surveyed their preference for the amount (5-point scale from very little to very much) and type (online tools and/or skills training) of communication support. Descriptive statistics were calculated. Findings: Across cases, most clinicians indicated to communicate about biomarker results (97-100% of clinicians), prognosis/dementia risk (79-98%), and prevention (90-99%), often tailored to patient characteristics and preferences. However, clinicians were more hesitant to explicitly mention the presence of AD in the SCD case (29%), compared to MCI (68%). Over half of clinicians indicated to prefer '(very) much' support regarding 9/10 listed communication skills, with highest percentages on: i) stimulating/ensuring patient's understanding of information provided (66%), ii) communicating with patients not (fluently) speaking their native language (66%), iii) communicating uncertainty (65%), iv) communicating about dementia risk (65%), and v) optimizing remote/online consultations (60%). They want support via online tools (34%), training (13%), or both (32%). Discussion: Clinicians have a positive attitude towards communicating early AD diagnosis, dementia risk, and prevention. Clinicians differ in how they explain the meaning of AD-biomarkers in early stages. We identified a need for communication support regarding a variety of skills. Fulfilling clinicians' needs might help to even better tailor memory clinic care to individual patients.